Досягнення у визначенні просторової структури білків на основі методів машинного навчання - Білецький, Б.О. (Кібернетика та комп’ютерні технології, 2021)
Мета роботи. Розглянути та проаналізувати основні принципі дії програмного комплекса AlphaFold з визначення просторової структури білків. Результати. Наведено основні складові методи та етапи в процесі розпізнавання структури білка. До складових етапів та відповідних методів належать такі як: пошук гомологічних білків на основі методів множинного вирівнювання, побудова білок-специфічного диференційованого потенціалу за допомогою штучних нейронних мереж та оптимізація енергії за допомогою градієнтного спуску та обмеженого семплювання. Цель работы. Рассмотреть и проанализировать основные принципы действия программного комплекса AlphaFold по определению пространственной структуры белков. Результаты. Приведены основные этапы в процессе распознавания структуры белка с помощью программного комплекса AlphaFold. Среди таких этапов поиск гомологичных белков на основе методов множественного выравнивания, построение белок-специфического дифференцируемого потенциала с помощью искусственных нейронных сетей и оптимизация энергии с помощью градиентного спуска и ограниченного сэмплирования. Purpose of the article. The aim of the work is to consider and analyze the basic principles of the AlphaFold software package for determining the spatial structure of proteins. Results. We consider the main stages in the process of recognizing the structure of a protein using the AlphaFold program complex. The stages and corresponding methods include: search for homologous proteins based on multiple alignment methods, construction of protein-specific differentiated potential using artificial neural networks and protein structure energy optimization using gradient descent and limited sampling. We discuss how combination of various bioinformatics techniques powered by data from open data sources can lead to significant improvements in accuracy of protein structure prediction. Special attention is paid to the use of artificial neural networks for building the smooth protein-specific potential and following energy minimization based on constructed potential.